2009
DOI: 10.1098/rstb.2009.0105
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual beginnings to learning words

Abstract: At the macrostructure level of language milestones, language acquisition follows a nearly identical course whether children grow up with one or with two languages. However, at the microstructure level, experimental research is revealing that the same proclivities and learning mechanisms that support language acquisition unfold somewhat differently in bilingual versus monolingual environments. This paper synthesizes recent findings in the area of early bilingualism by focusing on the question of how bilingual i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 100 publications
1
61
0
5
Order By: Relevance
“…For example, past research has found that bilinguals and monolinguals appear to learn words for concepts at approximately the same rate (De Houwer, Bornstein, & Putnick, 2013;Hoff et al, 2012; see also Cattani et al, 2014). Bilinguals and monolinguals also show similar capacities for mapping words to objects in the learning environment (Byers-Heinlein & Werker, 2013;Werker, Byers-Heinlein, & Fennell, 2009) and appear to learn their first words at approximately the same time (Vihman, Thierry, Lum, Keren-Portnoy, & Martin, 2007). Unfortunately, the difficulty of collecting bilingual data often limits inferences about the influence of early bilingualism to small samples.…”
Section: Cross-language Interactionmentioning
confidence: 88%
“…For example, past research has found that bilinguals and monolinguals appear to learn words for concepts at approximately the same rate (De Houwer, Bornstein, & Putnick, 2013;Hoff et al, 2012; see also Cattani et al, 2014). Bilinguals and monolinguals also show similar capacities for mapping words to objects in the learning environment (Byers-Heinlein & Werker, 2013;Werker, Byers-Heinlein, & Fennell, 2009) and appear to learn their first words at approximately the same time (Vihman, Thierry, Lum, Keren-Portnoy, & Martin, 2007). Unfortunately, the difficulty of collecting bilingual data often limits inferences about the influence of early bilingualism to small samples.…”
Section: Cross-language Interactionmentioning
confidence: 88%
“…During this period of broad perceptual sensitivity, bilingually-exposed infants differentiate and sort linguistic input based on features including vowel contrasts (Sebastián-Gallés and Bosch 2009; Sundara and Scutellaro 2010), consonant contrasts (Sundara et al 2008), and visible articulation cues (Pons et al 2009) to develop a foundation in two language systems. The perceptual 'tuning' that occurs before the end of the first year of life (Gervain and Werker 2008) reflects the infants' attention to contrasts that are relevant in their language system(s) and has an impact on word learning in typically-developing children: very young monolinguals appear to use different learning mechanisms to acquire words than their bilinguallyexposed peers (Werker et al 2009). It is possible that perceptual abilities and word-learning strategies may differ depending on whether a child with an ASD received bilingual or monolingual exposure during the first year of life.…”
Section: Introductionmentioning
confidence: 98%
“…The infant perception literature supports a general perceptual narrowing from 6 to 12 months of age as infants tune into the specific sensory input that characterizes their linguistic environment (Pons et al 2009). Many studies have demonstrated that typically-developing infants are sensitive to acoustic contrasts across languages that older children do not perceive; there appears to be a critical window for heightened speech perception and discrimination during the first year of life (Werker and ByersHeinlein 2008;Werker et al 2009;Werker and Tees 1984). During this period of broad perceptual sensitivity, bilingually-exposed infants differentiate and sort linguistic input based on features including vowel contrasts (Sebastián-Gallés and Bosch 2009; Sundara and Scutellaro 2010), consonant contrasts (Sundara et al 2008), and visible articulation cues (Pons et al 2009) to develop a foundation in two language systems.…”
Section: Introductionmentioning
confidence: 98%
“…Research exploring language processing in adult bilinguals has increased dramatically during recent years (Bialystok, 2010;Dupoux, Peperkamp, & Sebastián-Gallés, 2010;Wu & Thierry, 2010), but there is comparatively less work examining the development of phono-lexical processing in bilingual toddlers' language acquisition (but see Werker, Byers-Heinlein, & Fennell, 2009). Whereas some recent studies have investigated cognate processing and production in older bilingual children (e.g., Brenders, van Hell, & Dijkstra, 2011;Poarch & van Hell, 2012), the current study provides a novel examination of the language selectivity of lexical access (i.e., whether one or both languages of a bilingual are active during lexical processing) in bilingual toddlers.…”
Section: Introductionmentioning
confidence: 99%